Numerical simulation method for double shield TBMs crossing weak zones - Zhiwen Wang; Meng Wei; Yang Liu; Yushi Liu; Xinyu Tan; Xin Tong (Scientific Reports)
Abstract Deformation and collapse of the surrounding rock, leading to machine jamming, are critical factors hindering the safe and efficient operation of Double Shield Tunnel Boring Machines (DS TBMs). Machine jamming can be categorized into shield jamming and cutterhead jamming, each influenced by various factors. Numerical simulation effectively quantifies the impact of these factors. This paper examines the calculation methods for thrust resistance and cutterhead torque in DS TBMs and proposes a numerical simulation method that accounts for their tunneling process. A finite difference model of DS TBM excavation in rock with weak zones was developed in FLAC3D, incorporating interactions between the surrounding rock, TBM cutterhead, and shield. A Python program was created to extract stress data from individual shield and cutterhead elements, allowing for a precise quantitative assessment of potential jamming. The proposed numerical simulation method was validated for its accuracy and applicability through the analysis of a shield jamming incident at the K10 + 242 section of the DXL tunnel.